The Effect of Quizlet on Vocabulary Mastery of the Eight Grade Students’ of SMPU Al-Anwari Banyuwangi - Intan Alfina Damayanti; Sutami Dwi Lestari; Nur Hasibin (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2025)
Quizlet is one of the online-based language learning media in form of flashcards equipped with various features such as audio, pictures, words, quiz, and test. Research aimed to investigate whether there is any effect of Quizlet on students’ vocabulary mastery. The researcher found a problem with low English vocabulary mastery of students in class eight D, which has 18 students as respondents in this research. This research is an experimental research on vocabulary mastery of students in eighth grade students of SMPU Al-Anwari Kertosari Banyuwangi in the Academic Year 2023/2024. This research used the method of one-group pre-test post-test design. The instrument used for data collection in this research is multiple-choice test with total of 30 questions consisting of nouns and verbs. For the data analysis is used t-test formula. The researcher found there is increased post-test scores. The pre-test mean score was 69.778 and the post-test mean score was 85,555. In addition, in the T-test results, the t-test value is higher than t table. The t-test value was 3,086 and the t-table was 2.110 (3.086>2.110). The result of this research is that there is a significant effect of Quizlet on vocabulary mastery of students’ of SMPU Al-Anwari Banyuwangi.